Pendampingan Belajar Matematika Peserta Didik dalam Memahami Materi Persamaan Garis Lurus - Nur Miftahul Jannah; Hilmirrahma; St. Aswiah; Siti Sulaeha; Suharti (Faculty of Tarbiyah and Teacher Training, 2024)
Straight line equation is a subject matter that has some prerequisite material that must be understood so that students have difficulty in understanding the material. One of the causes of students having difficulty in understanding straight line equation material is due to students' lack of understanding of prerequisite material, namely cartesian diagrams, functions, and algebra. The service was carried out at MTs Madani Alauddin Po-pao class VIII C which aims to help students understand the straight line equation material by providing assistance to students. The service was carried out by mathematics education students and lecturers who were carrying out School Field Practices (PLP) 2 for 8 meetings by providing assistance to students during the learning process and working on assignments at the end of the meeting both personally and in groups in working on student worksheets at meetings 3 and 4. The results of the assistance show that the learning outcomes of students have increased, namely seen from the posttest results which show 27 students who fall into the medium to very high category which compared to the previous pretest results only 14 students fell into the medium to very high category. In addition, after conducting interviews, it is known that students like collaborative learning because the classroom atmosphere is interesting and do not feel awkward if there is something they want to ask. So that the service carried out with learning assistance has a positive impact on students in understanding the straight line equation material.